Factors Affecting Accounting Students' Interest in Online Learning in the Pandemic Period from the Perspective of Planned Behavior - Irvan Pratama Saputra; Bambang Tjahjadi (STAI Hubbulwathan Duri, 2022)
This study aims to examine the factors that influence accounting students' interest in online learning with the concept of planned behavior theory. The research variables consisted of attitudes, regulations, perceptions of control and interest in online learning. The research sample consisted of 150 accounting students in the city of Semarang, the data collection technique was using purposive sampling technique. Hypothesis test using multiple regression test and t test. The study's results accept the three hypotheses proposed and prove that the variables of attitude, regulation, and perception of control positively affect interest in online learning. The results of this study also strengthen that the theory of planned behavior can be used as an approach to explain the factors that influence individual interest in doing something.